Identification and analysis of the synergistic targets of TBX5 and GATA-4 - Patel, Bhakti R. (2011)
Cardiac development is a complex multi-step process involving a diverse network of genes. Defects in cardiac genes can lead to congenital heart defects (CHDs), and understanding the processes involved in normal cardiogenesis is crucial in elucidating the pathogenesis of disease. Mutations in a number of cardiac transcription factors have been associated with CHDs, including TBX5 and GATA-4. These transcription factors are high in the regulatory hierarchy and form a complex that is thought to direct and synergistically regulate common cardiac pathways. However, little is currently known about their joint targets. This study aimed to identify and analyse genes important in cardiogenesis, with focus on the combined targets of TBX5 and GAT A-4. Microarray expression analysis of TBX5/ GATA-4 double overexpression P19 cell lines led to the identification of a large number of genes, of which seven were selected for study; PA2.26, PETA-3, FUCA 1, FN, TPM1, DES, and RBMS1. Expression of these was confirmed in the embryonic chick heart at Hamburger and Hamilton (HH) stages 12 - 26. The cell cycle regulator and transcription factor RBMS1 was selected for investigation of its role in cardiac development. Morpholino knockdown of RBMS1 expression in the developing chick resulted in defects in cardiac looping and atrial septation. Whilst further work is required to strengthen this data, this is a novel finding and opens up possibilities for future research into cardiac transcriptional networks.